2015
DOI: 10.3390/ma8095288
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Gingival Fibroblasts on Zirconia Surfaces Containing Niobium Oxide

Abstract: It was indicated that tetragonal zirconia polycrystal (TZP) containing yttria (Y2O3) and niobium oxide (Nb2O5) ((Y,Nb)-TZP) could be an adequate dental material to be used at esthetically important sites. The (Y,Nb)-TZP was also proved to possess its osteogenic potential comparable with those conventional dental implant material, titanium (Ti). The objective of the current study was to characterize cellular response of human gingival fibroblasts (HGFs) to smooth and rough surfaces of the (Y,Nb)-TZP disc, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…There are many studies comparing zirconia with titanium [49,50,63,64], but only a few have compared CAD/CAM-ceramics with CAD/CAM-polymers. Raffaeli et al compared the response of rat immortalised fibroblasts to zirconia and feldspathic ceramics, and their findings suggested a better viability in zirconia.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies comparing zirconia with titanium [49,50,63,64], but only a few have compared CAD/CAM-ceramics with CAD/CAM-polymers. Raffaeli et al compared the response of rat immortalised fibroblasts to zirconia and feldspathic ceramics, and their findings suggested a better viability in zirconia.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus about which is the best surface to create a good mucosal seal and reduce bacterial adhesion. Some authors have reported the importance of this surface being smooth [ 8 , 11 , 39 , 42 ], while other authors have shown that rough surfaces are preferred, either through some surface treatment like sandblasting—with random cell growth—[ 7 , 45 ], or the creation of micro-roughness [ 5 ] to enhance attachment, proliferation, and spreading in the direction of the microgrooves.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, early cellular response in zirconium has been compared with multiple restoration materials, such as feldspathic ceramics [ 9 , 10 ] or titanium [ 7 , 8 ]. In vitro, zirconium is considered the alternative to titanium in terms of better maintenance of soft tissue stability, since it provides better biocompatibility and aesthetics [ 1 , 9 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two cell types create the barrier. The cells’ adhesion depends on various components such as lipids, carbohidrats and bound proteins [6,24,25,26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%